Monitoring Ruangan Berbasis Internet of Things Menggunakan Thingsboard dan Blynk - Yudi Eko Windarto; Bryan Monang Wiener Samosir; Muhammad Richie Assariy (Universitas Islam Negeri Walisongo Semarang, 2020)
Technology designed to facilitate humans in a variety of work. A very popular technology today is the Internet of Things. The application of Internet of Things technology is widely used in various fields at present. One was used to monitor the room. The methodology used in this study is a Hardware Development Life Cycle (HDLC). The results of this research that the device can transmit ambient conditions via the Internet of Things with protocol Message Queuing Telemetry Transport (MQTT). In this study, Raspberry Pi serves as an intermediary between the media data is read by the sensor is then stored on the application Thingsboard. In addition the application Blynk used as a medium for monitoring the device remotely.